Pengaruh Kebijakan Hutang Dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Br. Tarigan, Almaura Andinna; Silaban, Adanan; Siahaan, Audrey Margareth (CV. ITTC INDONESIA, 2024)
This study aims to examine the effect of debt and profitability policies on company value in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. The sampling technique uses the purposive sampling method. The total research sample is 81 companies with 3 years of research. This research is a quantitative research. The type of data carried out in this study is secondary data, which is in the form of financial statements and annual reports of food and beverage companies. The analysis method used is multiple linear regression using SPSS version 26 software. Data testing was carried out using descriptive statistical analysis, classical assumption test, multiple regression analysis test, determination coefficient and t-test. Meanwhile, profitability has a significant effect on the company's value